The effect of mentoring roles displayed by teaching staff on emotional and social loneliness levels of teacher candidates - Cankaya, Ibrahim Halil; Karakus, Mehmet; Demirtas, Zuelfue (Elsevier Science Bv, 2009)
In this study, it was aimed to determine the effect of mentoring roles in terms of integrity, relationship and guidance displayed by teaching staff on emotional and social loneliness levels of teacher candidates. Hierarchical multiple linear regression results showed that integrity and relationship dimensions of mentoring roles displayed by teaching staff have a significant effect on social loneliness levels of teacher candidates. However, none of the dimensions of mentoring roles have a significant effect on emotional loneliness levels of teacher candidates. Implications of findings for teacher training system are discussed. (C) 2009 Elsevier Ltd. All rights reserved
World Conference on Educational Sciences -- FEB 04-07, 2009 -- Nicosia, CYPRUS
Keywords: Mentoring; emotional loneliness; social loneliness